THE PSYCHOLOGICAL ANALYSIS OF VERBAL AND NON-VERBAL INTELLIGENCE OF STUDENTS IN PSYCHOLOGY - Tokareva, Natalya; Shamne, Anzhelika (PSYCHOLOGICAL JOURNAL, 2019)
The article studies the features of psychology students’ intelligence structure within the integrative approach. An individual’s intellectual development is considered by the authors as an indicator of the quality of specialists’ professional training at universities. The empirical research purpose was to determine the fundamental tendencies in the structural elements of the intelligence for the students majoring in the "Social and Behavioural Sciences" subject area (the “Psychology” specialty; n = 22) with the aim to find the vectors for the formation of future specialists’ optimal professional profile. The sample also included the groups of students in the humanities (the "English/German language and literature" specialty; n = 18) and the social sciences (the "History" specialty; n = 22). For intelligence diagnosing, Amthauer’s intelligence structure test (IST) was used, in particular, its subtests for the verbal intelligence (“Logical Choice”, “Word Exclusion”) and for the non-verbal one (“Numerical series”, “Figure Choice”). There are no statistically significant differences as for verbal intelligence between psychology students and non-psychology ones. Instead, statistically significant differences for the non-verbal intelligence indicators, including mathematical ones, were recorded. Psychology students have a higher level of combinatorial-logical and inductive reasoning, numeracy capabilities, etc. The most significant differences between the investigated groups were recorded in the system of relationships between verbal and non-verbal intelligence indicators. Unlike the students in humanities and those in non-psychology social sciences, psychology students have close links between verbal and non-verbal intelligence indicators in their intelligence structure. The conclusion was drawn that mathematical abilities are part of the structure of professionally significant intellectual qualities of future psychologists, as well as the conclusion about the presence of relations between intellectual abilities of psychology students and their professionalization at university. The psychological and pedagogical conditions for the efficient formation of professionally determined intellectual abilities of future psychologists in the system of professional training are outlined.